Technology Acceptance Model (Tam) Untuk Mengukur Tingkat Kepuasan Terhadap Penerapan Aplikasi Merdeka Mengajar - Oktiana, Ekal; Latuperissa, Rudy (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This research aims to assess the level of satisfaction of teachers at PC HIMPAUDI Kedungbanteng regarding the use of the Merdeka Mengajar application using the Technology Acceptance Model (TAM). The Technology Acceptance Model (TAM) was chosen because it has been proven effective in assessing user satisfaction and can explain various aspects of usability and ease of use in advances in information technology. Analysis using the Technology Acceptance Model (TAM) involves five variables, namely Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention to Use (BITU), Actual Usage Behavior (AUB). The sample for this research was determined using the Slovin formula, involving 38 teachers at PC HIMAPUDI Kedungbanteng. Data obtained through distributing questionnaires was measured using a Likert scale. The test results for the five variables stated that the user was satisfied. However, several problems were discovered in order to gain a deeper understanding and solutions to improve the user experience in the future as well as improving infrastructure and application performance to ensure the Merdeka Mengajar Application can be used optimally by teachers, especially in areas with limited internet connections.